Помогите срочно! Кто нибудь!

0 голосов
21 просмотров

Помогите срочно! Кто нибудь!


image

Алгебра (241 баллов) | 21 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

\frac{3}{x-3} - \frac{x+15}{ x^{2} -9} - \frac{1}{x} = \frac{3x(x+3)-x(x+15)-( x^{2} -9)}{x(x-3)(x+3)} = \frac{ 3x^{2}+9x- x^{2} -15x- x^{2} +9 }{x(x-3)(x+3)}
= \frac{ x^{2} -6x+9}{x(x-3)(x+3)} = \frac{ (x-3)^{2} }{x(x-3)(x+3)} = \frac{(x-3)(x-3)}{x(x-3)(x+3)} = \frac{x-3}{x(x+3)} = \frac{x-3}{ x^{2} +3x}
(7.2k баллов)